2009
DOI: 10.1073/pnas.0810496106
|View full text |Cite
|
Sign up to set email alerts
|

Gamma flicker triggers attentional selection without awareness

Abstract: Gamma band modulations in neural activity have been proposed to mediate attentional processes. To support a causal link between gamma activity and attentional selection, we attempt to evoke gamma oscillations by a 50-Hz subliminal flicker. We find that a subliminal 50-Hz flicker at a target location, before target presentation, speeds up and enhances target detection and discrimination. This effect is specific to the middle of the gamma range because it is not evident at <35-Hz flicker. It requires 300 ms to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 36 publications
5
65
3
Order By: Relevance
“…The reason is that reactive modification of processing following a misguiding visual prime would be much harder with invisible than with visible stimuli (see Ansorge, Heumann, & Scharlau, 2002;Cheesman & Merikle, 1985). Ivanoff and Klein (2003) observed that after initial capture by invisible stimuli, attention could not be deallocated from the position of the capturing stimulus within 300 msec (see also Bauer, Cheadle, Parton, Müller, & Usher, 2009). Likewise, Ansorge et al (2002) found that the pace of learning to deallocate attention from an irrelevant singleton was proportional to the singleton's visibility.…”
Section: Methodsmentioning
confidence: 99%
“…The reason is that reactive modification of processing following a misguiding visual prime would be much harder with invisible than with visible stimuli (see Ansorge, Heumann, & Scharlau, 2002;Cheesman & Merikle, 1985). Ivanoff and Klein (2003) observed that after initial capture by invisible stimuli, attention could not be deallocated from the position of the capturing stimulus within 300 msec (see also Bauer, Cheadle, Parton, Müller, & Usher, 2009). Likewise, Ansorge et al (2002) found that the pace of learning to deallocate attention from an irrelevant singleton was proportional to the singleton's visibility.…”
Section: Methodsmentioning
confidence: 99%
“…Attentional modulation by external oscillations is not a mandatory prediction of temporal tagging (one could imagine that peripheral filters were set up to prevent any ''bleed through'' of external oscillations), but it is certainly consistent with the hypothesis, and any observation of such influences would be difficult to explain in a pure rate model. This is where the Bauer et al study (1) comes in. In their first experiment, the amplitude of a visual stimulus is modulated in the gamma range, and they show that this modulation enhances its detectability and discriminability, as if it received more attentional resources.…”
Section: Attended Stimuli Might Be Distinguished From Unattended Stimmentioning
confidence: 99%
“…Selective attention is the triage process of extracting the most relevant sensory information and suppressing the remainder. In a recent issue of PNAS, through an ingenious psychophysical experiment, Bauer et al (1) provide insight into the mechanisms underlying this cognitive function.…”
mentioning
confidence: 99%
“…From the different frequency bands, gamma oscillations have most consistently been associated with attention (Bauer, Cheadle, Parton, Müller, & Usher, 2009;Womelsdorf & Fries, 2007). The relevance of these oscillations, if any (Pareti & DePalma, 2004), remains a matter of debate.…”
Section: Oscillations In Biological Neural Networkmentioning
confidence: 99%